Alternative frameworks for providing financial services - Claessens, Stijn, 1959- 1959- (Policy research working paper, 1999)
The behavior of actors in financial systems depends crucially on the incentives that motivate them. The right regulation, supervision, and incentives (including the scope of permissible activities, degree of contestability, and extent of safety net) for financial services can make the sector more resilient in the face of adverse shocks